HipHop2SToP a community-led health promotion initiative empowering Aboriginal youth in the Kimberley region of Western Australia: a process evaluation - McRae, Tracy; Walker, Roz; Enkel, Stephanie; Thomas, Hannah M. M.; Jacky, John; Sibosado, Slade; Mullane, Marianne; Maginnis, Natasha; Coffin, Juli; Carapetis, Jonathan R.; Bowen, Asha C. (Frontiers in Public Health, 2023)
Introduction For millennia, Aboriginal people’s ways of knowing, doing and being were shared through art, song, and dance. Colonisation silenced these ways, affecting loss of self-determination for Aboriginal people. Over the past decade in Australia, hip-hop projects have become culturally appropriate approaches for health promotion. When community led, and Aboriginal worldviews centralised, hip-hop workshops are more likely to be effective. In 2020, during the COVID-19 pandemic, a community-led health promotion hip-hop music video, ‘HipHop2SToP’ was produced involving young people in Dampier Peninsula communities address healthy skin and healthy living practices. Methods We report here a qualitative process evaluation of the HipHop2SToP project. Participants who had been involved in the planning and production of HipHop2SToP were selected using a purposive approach and invited either by email or face-to-face to participate in semi-structured interviews and share their experiences. Semi-structured interviews ranged from 30 to 60 min in duration and were conducted either face-to-face or virtually over MS Teams. Due to personal time constraints, two participants provided written responses to the semi-structured questions. All interviews were audio-recorded with consent and saved as a digital recording in a de-identified format. All audio recordings were transcribed verbatim and uploaded into QSR NVivo v12 along with written responses. Results As a health promotion project, the critical success factors were community-ownership and discovering novel ways to collaborate virtually with remote communities using Microsoft (MS) software. Highlights included observing the young people actively engaged in the project and their catchy lyrics and key messaging for environmental health and skin infections. COVID-19 presented some challenges. Gaps in communication, clarification of stakeholder roles and expectations, and post-production outcomes were also identified as challenges. Conclusion HipHop2SToP validates the need for Aboriginal community led health promotion programs. While creating some challenges COVID-19 also strengthened community ownership and created novel ways of maintaining relationships with remote Aboriginal communities. Future hip-hop projects would benefit from clarity of roles and responsibilities. Strengthening post-production outcomes by including a launch and well-planned, targeted communication and dissemination strategy will ensure the wider translation of important health messages and potential strengthen sustainability.